Hydrophobic Triaryl‐Substituted β‐Lactams as Activity‐Based Probes for Profiling Eukaryotic Enzymes and Host–Pathogen Interactions. Issue 15 (1st September 2014) - Nasheri, Neda; McKay, Craig S.; Fulton, Kelly; Twine, Susan; Powdrill, Megan H.; Sherratt, Allison R.; Pezacki, John Paul
<x xml:space="preserve">Abstract</x> ABPP with β‐lactams: We identified the eukaryotic targets of β‐lactam‐containing compounds by activity‐based protein profiling. Using this method, we demonstrated that β‐lactam‐based activity probes can be applied to identify differentially active enzymes in different cell lines and during hepatitis C virus replication.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>